Analisis Strategi Bauran Pemasaran (Marketing Mix) UMKM Gula Semut Sari Aren Desa Air Meles Ataskecamatan Selupu Rejang Kabupaten Rejang Lebong - Armiya Yuniarti; Gracia Gabrienda; Mira Yanuarti (Politeknik Kampar, 2025)
Marketing Mix is ??a combination of marketing activities carried out by companies to market certain goods and services during a certain period of time and a certain market. The purpose of this study was to determine the internal factors and external factors encountered in the application of the marketing mix (Marketing Mix) at Semut Sari Aren Sugar UMKM AND To find out and identify the application of the marketing mix (Marketing Mix) at Semut Sari Aren Sugar UMKM. This research was carried out in June - July 2023 on Jl Pramuka No. 5 Hamlet I Air Meles Atas, Selupu Rejang District, Rejang Lebong Regency. This research method uses the IFE, EFE, SWOT analysis and 7p marketing mix methods. The results of this study are the internal factors that are the main strength in the UKM Sari Aren Sugar Ants in Air Meles Atas Village, Selupu Rejang District, Rejang Lebong Regency, namely a competent workforce, the availability of a lot of raw materials for palm sugar and palm sugar products which have different characteristics from other products. other sugar. Weakness factors consisting of the lack of interest in buying by the local community, and limited market information and limited capital. External factors that become opportunities for the Semut Sari Aren Sugar MSMEs in Air Meles Atas Village, Selupu Rejang District, Rejang Lebong Regency are the support from the government, the development of science and technology in supporting the formation of the sugar palm agroindustry, and exhibitions held by the government to market palm sugar products. Factors that pose a threat are consumer demands for quality, demands for high export quality standards and changing seasons.